Direct Synthesis of α-Silicon Nitride Nanowires from Silicon Monoxide on Alumina - Jiang Cui; Bin Li; Chunrong Zou; Changrui Zhang; Siqing Wang (Nanomaterials and Nanotechnology)
Silicon nitride nanowires were synthesized using silicon monoxide as raw materials and an alumina plate as substrate at 1500°C. The obtained nanowires were characterized by X-ray diffraction, Fourier transform infrared spectrosco‐ py, scanning electron microscopy, high-resolution trans‐ mission electron microscopy and thermogravimetric- differential scanning calorimetry. The results revealed that silicon nitride nanowires possess a diameter of about 200 nm and a length of several hundred micrometres. The preferred growth direction of the nanowires was [100]. The chemical and structural composition of the silicon nitride nanowires were also studied and were shown to have a composition of primarily α-Si3N4. The temperature for fierce oxidation in air was above 1135°C. The formation mecha‐ nism of silicon nitride nanowires was assumed to be a vapour-solid (VS) process.